DUKUNGAN KELUARGA DALAM MENINGKATKAN HARGA DIRI LANSIA - Susilowati, Susilowati; Sari, Diana (Akademi Keperawatan Pamenang, 2014)
Family support is needed by the elderly so that the elderly do not feel Low self. The support can be either help or assistance when the elderly need, sometimes the support it will not appear if a family does not understand the needs of the elderly . The objective of this research was to describe family support in increasing the self-esteem of elderly .This research design used descriptive, the population was families with elderly. technique used purposive sampling by using inclusive and exclusive criteria.The research results obtained that 21 respondents (58.3 %) gave less support to the informational support, 21 respondents (58.3 %) gave less support to support assessment , 25 respondents (69.9 %) provide sufficient support to the Instrumental support , 18 respondents (50 %) provide less support for the emotional support , while almost half over respondents with primary educated amount to 21 respondentsÂ (58.3 %) .It is concluded that family support to the elderly are included in the enough category that is only in instrumental support, because the respondents have a view that the elderly need only fulfillment of the needs of food and clothing and shelter only, it is necessary to regularly counseling by health workers to the families so that adds to the knowledge of the respondents.Â Keywords: family support, self esteem, elderly.